Functionalization of carbonaceous materials for photovoltaic devices - Mamo, Messai Adenew (My University, 2011)
A C60-cyclopentadiene cycloadduct was readily synthesized, by a Diels-Alder reaction between C60 and freshly cracked cyclopentadiene. The functionalized C60 and norbornene were then pre-mixed in varying molar ratios and co-polymerized using a ROMP approach with catalytic amounts of Grubbs second generation catalyst. A series of C60-containing polymers were also synthesized by the co-polymerization of a C60-cyclopentadiene cycloadduct and N-(cycloheptyl)-exo-norbornene-5,6-dicarboximide in varying ratios using similar procedures. The polymerization was facilitated by use of a catalytic amount of Grubbs second generation catalyst. The C60 co-polymers formed were investigated by FT-IR, UV-visible, 1H NMR and 13C NMR spectroscopy, mass spectrometry, differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA). Functionalization of C60 was achieved by using a 1,3-dipolar addition of azomethine ylides to C60 that resulted in fulleropyrrolidines containing 2- and 3-thiophenecarboxaldehyde. Finally, the two C60 derivatives, together with different ratios of either thiophene or 3-hexylthiophene, were oxidatively copolymerized using FeCl3 as catalyst. Either nitrogen-doped or undoped carbon nanotubes were synthesized from ferrocene, pyridine and toluene and decomposition of acetylene over a catalyst respectively, were functionalized using azomethine ylides from the thermal condensation of N-methylglycine and 5-norbornene-2-carboxaldehyde. The polymerization from the side walls of the carbon nanotubes using bicyclo[2.2.1]hept-2-ene as a monomer was achieved using the Grubbs‟ second generation catalyst. The synthesised CNTs and polymer-attached carbon nanotubes were subsequently characterised. The attachment of different organic functional groups to the carbon nanotubes from the thermal condensation of N-methylglycine and 2-thiophenecarboxaldehyde was achieved. The functionalized carbon nanotubes, and either thiophene or 3-hexylthiophene were used in copolymerization reactions by oxidative polymerization, using FeCl3 as catalyst. The copolymers containing the nanotubes, were found to be more regioregular than pure poly(3-hexylthiophene). The synthesised CNTs and polymer-attached carbon nanotubes were then characterised. The thiophene-based C60-copolymers and thiophene polymer-attached CNTs, with and without TiO2, were deposited on the surface of TiO2 paste with, and without, dye impregnation. A sandwich-type cell made from a TiO2 thin film electrode with, and without, dye impregnation, ionic liquid electrolytes and a Pt-coated fluoride tin oxide (FTO) counter electrode was prepared. Both organic and dye sensitized solar cells (DSSC) were subsequently assembled. The efficiency, current densities, open circuit voltages and fill factors were found to decrease as the concentration of C60 derivative in the copolymer decreased. Furthermore, pre-mixing the copolymers with TiO2 nanoparticles improved the overall performance of the photo cell. In addition, the polymer-attached N-doped CNTs performed better in the photo cells than polymer-attached undoped CNTs.